2016
DOI: 10.1002/2016ja022973
|View full text |Cite
|
Sign up to set email alerts
|

Control of the innermost electron radiation belt by large‐scale electric fields

Abstract: Electron measurements from the Magnetic Electron Ion Spectrometer instruments on Van Allen Probes, for kinetic energies ∼100 to 400 keV, show characteristic dynamical features of the innermost ( L≲1.3) radiation belt: rapid injections, slow decay, and structured energy spectra. There are also periods of steady or slowly increasing intensity and of fast decay following injections. Local time asymmetry, with higher intensity near dawn, is interpreted as evidence for drift shell distortion by a convection electri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
59
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(61 citation statements)
references
References 38 publications
2
59
0
Order By: Relevance
“…It can also be used to question the suitability of different electric field models in the low-L region [e.g., Ridley et al, 2014;Selesnick et al, 2016]. We obtained excellent agreement between the two probes, especially below L~2.…”
Section: 1002/2016ja023613mentioning
confidence: 62%
See 1 more Smart Citation
“…It can also be used to question the suitability of different electric field models in the low-L region [e.g., Ridley et al, 2014;Selesnick et al, 2016]. We obtained excellent agreement between the two probes, especially below L~2.…”
Section: 1002/2016ja023613mentioning
confidence: 62%
“…For instance, structured energy spectra called zebra stripes have been reported for both trapped energetic electrons [Imhof and Smith, 1965] and ions [Williams and Frank, 1984]. Although the existence of enhanced radial diffusion is now well accepted and documented [Farley, 1969;Selesnick, 2012;Zhao and Li, 2013], it remains uncertain how (and how fast) trapped particles are transported through drift shells in the low-L region [e.g., Selesnick et al, 2016;O'Brien et al, 2016]. Although different theories were proposed [e.g., Pinto et al, 1991;Sauvaud et al, 2013;Ukhorskiy et al, 2014;Lejosne and Roederer, 2016;Liu et al, 2016], it is still unclear what the mechanisms for the generation of zebra stripes really are.…”
Section: 1002/2016ja023613mentioning
confidence: 99%
“…Radial diffusion coefficients that have been estimated from observed apparent lifetimes (e.g., Selesnick, , ) may include effects from neoclassical diffusion that we are trying to model in this paper, or may be due to radial diffusion of the type described by Fälthammar (), or may be a combination of both types of radial diffusion. Selesnick et al () used the observed magnetic local time dependence of particle distributions to infer electric‐field amplitudes that were used to estimate radial diffusion coefficients of the type described by Fälthammar () and concluded that this could explain the apparent lifetimes observed in previous work. Lejosne and Mozer () have shown that electric fields may be inferred from Van Allen Probes measurements, with careful analysis, down to L = 1.2.…”
Section: Discussionmentioning
confidence: 99%
“…Several physical mechanisms have been proposed to explain the deep penetration of protons and electrons into the low L region (e.g., Califf et al, ; Korth et al, ; Li et al, ; Lyons & Thorne, ; Reeves et al, ; Ripoll et al, ; Selesnick, Su, & Blake, ; Su et al, ; Turner et al, , 2017; Zhao & Li, ). The most prevalent mechanisms include shock‐induced energization, substorm injections, inward radial diffusion, convection of plasma sheet particles, and transport of trapped energetic particles by enhanced large‐scale convection electric field.…”
Section: Potential Mechanisms Of Deep Penetration Event On 8 April 2016mentioning
confidence: 99%